Field notes contributed by Ted LaGrange, summer 1985 - LaGrange, Tedet al (1985)
List of birds and locations contributed by Ted LaGrange. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of summer 1985. Epson - sheet feed/flatbed